The properties of inflation expectations: Evidence for India - Naresh Kumar Sharma; Motilal Bicchal (EconomiA, 2018)
Empirical inferences about particular forms of agents' inflation expectations are crucial for the conduct of monetary policy. This paper is an attempt to explore the properties of the Reserve Bank of India's survey data of households' inflation expectations. The paper shows that survey respondents do not form expectations rationally, regardless of the reference measures of inflation used. Further, results indicate that inflation expectations are formed purely in backward-looking manner, suggesting that the Reserve Bank of India (RBI) has a low degree of credibility within the survey respondents. The study then formulates a model to identify individual elements of the backward-looking expectations in the data. The results suggest that the respondents' short term expectations for WPI inflation are purely naïve type of expectations, only influenced by respondents earlier period expectations. In the case of CPIIW inflation, the results however suggest that the short-term expectations are not purely naïve type, but also contain adaptive as well as a static forms of expectations. This means that respondents consider their previous forecast errors about CPIIW inflation and draw recent price developments in the CPIIW while forming their overall short-term inflation expectations. This finding provides some formal evidence that the CPI based inflation measure is better suited, than WPI inflation, as a nominal anchor in the RBI's recent transition to inflation targeting regime.
Keywords: 330; Inflation; Inflation expectations; Survey data; Price index; Monetary policy; Forecasting